The influence of a thin, natural cellulose fibre membrane on the acoustic absorption of a layer of melamine foam. Issue 2 (June 2023) - Xu, Wenhao; Horoshenkov, Kirill V; Jin, Yun
Porous materials such a melamine foam are commonly used to absorb noise and to control reverberation time in buildings. However, the ability of a thin porous layer to absorb noise at acoustic wavelengths that is much greater than the layer thickness is limited. This work investigates theoretically and experimentally the influence of a very thin, natural cellulose membrane on the sound absorption coefficient of a melamine foam substrate. The experimental results demonstrate that the presence of a 120 μm cellulose membrane can more than double the sound absorption coefficient of a relatively thin (17.4 mm) layer of melamine foam at frequencies above 600 Hz (577 mm wavelength). The theoretical part of work explains this effect through a careful simulation. The results show that there are analytical models that can accurately predict the acoustical behaviour of the cellulose membrane combined with a layer of melamine foam. The effects of the flow resistivity and thickness of a cellulose fibre membrane on the acoustic absorption coefficient of the melamine foam substrate are also studied through modelling and experiment. It is found that the optimum thickness of the cellulose fibre membrane should be between 75 and 100 µm when laminated on the top of a 20 mm melamine foam substrate. This work suggests that thin layers of sustainable natural materials such as cellulose fibres can be used to significantly improve the ability of traditional porous media to absorb sound.